Solid acid alkylation catalyst as well as preparation method and application thereof

By using aluminum-based sieve catalyst and hydrolysis reaction method, the problems of low active component content and poor dispersion of binder are solved, and efficient catalyst preparation and excellent catalytic performance are achieved.

CN119897147AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311413627.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

During the molding process of existing molecular sieve catalysts, there are problems such as low active component content and poor dispersion of binder, which affects the catalytic performance.

Method used

Using a solid acid alkylation catalyst including molecular sieve and aluminum-based binder, the hydrolysis reaction and molding of the organic aluminum-alkane binder precursor solution is mixed with the molecular sieve to carry out hydrolysis reaction and molding.

Benefits of technology

The content of active components in the catalyst and the dispersion of the binder are improved, the unit cell constant of the molecular sieve and the microporous structure of the catalyst are maintained, and the catalytic performance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897147A_ABST
    Figure CN119897147A_ABST
Patent Text Reader

Abstract

The invention relates to the field of molecular sieve catalysts and discloses a solid acid alkylation catalyst as well as a preparation method and application thereof. The solid acid alkylation catalyst comprises a molecular sieve and an aluminum-based adhesive, by taking the total amount of the catalyst as a reference, in the catalyst, w (Al2O3) is more than or equal to 10% and less than or equal to 40%, w (Al2O3) represents the mass fraction of Al2O3 in the catalyst measured by an XRF (X-Ray Fluorescence) method, and Al2O3 comprises aluminum oxide in the aluminum-based adhesive and aluminum oxide in the molecular sieve; the d value of the catalyst is less than or equal to 10nm, and the d value represents the thickness, measured by a TEM (Transmission Electron Microscope) method, of the aluminum-based adhesive outwards along the edge of the crystal face of the molecular sieve crystal grain in the catalyst. The catalyst has high active component content and excellent adhesive dispersibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular sieve catalysts, and in particular to a solid acid alkylation catalyst and a preparation method and application thereof. Background Art

[0002] Molecular sieve catalysts have the advantages of regular crystal structure, uniform microporous structure, huge specific surface area, multiple acid sites, good hydrothermal stability, and easy regeneration. They are widely used in petrochemical and fine chemical product synthesis industries. However, different types of reactions have different requirements for the acid structure of molecular sieve catalysts, which puts higher requirements on molecular sieve catalysts. Recent studies have found that adding additives such as binders can improve the acid structure of molecular sieves to a certain extent.

[0003] Chinese patent application CN105688977A discloses a method for preparing a catalytic cracking catalyst containing pseudo-boehmite. The pseudo-boehmite is modified with silicon, the mixing and stirring time of the silicon-containing solution and the pseudo-boehmite is controlled, and the peptization performance thereof is adjusted, thereby controlling the wear index of the catalytic cracking catalyst and increasing the pore volume of macropores above 100 nm.

[0004] Chinese patent application CN106268724A discloses a catalyst containing molecular sieves and alumina. The catalyst carrier contains alumina and two Y-type molecular sieves. Based on the carrier, the total content of the Y-type molecular sieve is 5% to 70% by weight, and the content of alumina is 30% to 95% by weight. It is characterized in that the carrier is obtained by mixing, molding, drying and calcining the Y-type molecular sieve and pseudo-boehmite. The pseudo-boehmite includes PB1, characterized by X-ray diffraction, and the κ1 and κ2 of the PB1 are respectively greater than 1 and less than or equal to 3, wherein κ1=h2 / h1, κ2=h3 / h2, and h1, h2 and h3 are respectively the peak heights of the three diffraction peaks in the X-ray diffraction spectrum of PB1 at 2θ angles of 24-30°, 35-41° and 46-52°. The selectivity, activity and stability of the catalyst carrier are regulated by modifying the properties of the pseudo-boehmite.

[0005] In the traditional preparation method of molecular sieves, active components, clay or binders, and additives are generally mixed and then a molding method is used to obtain a molded carrier to maintain the strength and size requirements of the molecular sieve. The content of the active components of the molecular sieve in the mixture is required to be low (generally less than 70%), and the added binder must be mixed evenly to obtain a good bonding effect. It will also introduce a mesoporous structure into the catalyst, changing the microporous structure of the catalytic material and thus affecting its catalytic properties. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art in the molecular sieve catalyst forming process and to provide a solid acid alkylation catalyst and a preparation method and application thereof. The catalyst has a high active component content and excellent binder dispersibility.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a solid acid alkylation catalyst, wherein the catalyst comprises a molecular sieve and an aluminum-based binder, and based on the total amount of the catalyst, in the catalyst, 10%≤w(Al2O3)≤40%, w(Al2O3) represents the mass fraction of Al2O3 in the catalyst measured by an XRF method, and the Al2O3 comprises aluminum oxide in the aluminum-based binder and aluminum oxide in the molecular sieve; the d value of the catalyst is ≤10nm, and the d value represents the thickness of the aluminum-based binder in the catalyst along the crystal face edge of the molecular sieve grain outward measured by a TEM method.

[0008] Preferably, the d value of the catalyst is 0.01-5 nm, more preferably 0.01-1 nm.

[0009] Preferably, the aluminum-based binder contains at least a portion of free aluminum oxide, and preferably, the catalyst does not contain free aluminum oxide with a particle size exceeding 0.1 nm.

[0010] A second aspect of the present invention provides a method for preparing a solid acid alkylation catalyst, wherein the method comprises the following steps:

[0011] (1) subjecting a solid-liquid mixture containing a binder precursor solution and a molecular sieve to a hydrolysis reaction with water, and then performing solid-liquid separation to obtain a solid mixture;

[0012] (2) mixing the solid mixture of step (1) with a peptizing agent, an auxiliary agent and water to form a solid acid alkylation catalyst after drying and calcining;

[0013] The binder precursor is selected from at least one of organic alcohol aluminums.

[0014] The third aspect of the present invention provides a solid acid alkylation catalyst prepared by the preparation method described in the second aspect.

[0015] The fourth aspect of the present invention provides a use of the solid acid alkylation catalyst described in the first aspect or the third aspect in an alkylation reaction.

[0016] The catalyst provided by the present invention can realize catalyst molding using less binder, which ensures that the unit cell constant of the molecular sieve in the catalyst does not decay as much as possible, and the binder is highly dispersible. Preferably, the catalyst has a higher micropore ratio and a higher acid content, which can keep the skeleton aluminum from being lost and ensure the strength of the catalyst.

[0017] The method provided by the present invention comprises the following steps: mixing an organic alcohol aluminum binder precursor solution with a molecular sieve, and then hydrolyzing and molding the mixture to obtain a catalyst; selecting the organic alcohol aluminum binder precursor solution and the molecular sieve for mixing can improve the degree of dispersion of the binder and ensure the dispersibility of the binder in the catalyst; further, by first mixing the organic alcohol aluminum binder precursor solution with the molecular sieve and then adding water for hydrolysis reaction, the binder precursor is highly dispersed during the mixing process; a subsequent hydrolysis reaction generates a water-phase pseudo-boehmite with a high-quality pore structure, so that the catalyst can maintain a good microporous structure and acidity during the subsequent molding preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the TEM-EDX spectrum analysis diagram of the catalyst in Example 1 ( Figure 1 A is the TEM image of the catalyst. Figure 1 B is the distribution diagram of aluminum element. Figure 1 C is the distribution diagram of silicon element. Figure 1 D in the figure is the overlapping distribution diagram of silicon and aluminum elements);

[0019] Figure 2 This is the TEM-EDX spectrum analysis diagram of the catalyst in Comparative Example 1 ( Figure 2 A is the TEM image of the catalyst. Figure 2 B is the distribution diagram of aluminum element. Figure 2 C is the distribution diagram of silicon element. Figure 2 D in the figure is the overlapping distribution diagram of silicon and aluminum elements);

[0020] Figure 3 The MAS NMR of the catalysts of Example 1 and Comparative Example 1 is 27 Al spectrum. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The first aspect of the present invention provides a solid acid alkylation catalyst, wherein the catalyst includes a molecular sieve and an aluminum-based binder. Based on the total amount of the catalyst, in the catalyst, 10%≤w(Al2O3)≤40%, w(Al2O3) represents the mass fraction of Al2O3 in the catalyst measured by an XRF method, and the Al2O3 includes aluminum oxide in the aluminum-based binder and aluminum oxide in the molecular sieve; the d value of the catalyst is ≤10nm, and the d value represents the thickness of the aluminum-based binder in the catalyst along the crystal face edge of the molecular sieve grain outward, measured by a TEM method.

[0023] In the present invention, W(Al2O3) is measured by semi-quantitative element analysis using a ZSX100E X-ray fluorescence spectrometer produced by Rigaku. The specific test conditions are: tungsten target (excitation voltage 40kV, excitation current 250Ma). The sample powder is pressed into tablets, and the applied pressure is generally 500-1000KPa.

[0024] In the present invention, the d value is measured by using a JEM-ARM200F spherical aberration corrected transmission electron microscope. The specific test method is: the sample is uniformly dispersed with ethanol and then dripped onto the carbon film and dried, and then tested. The acceleration voltage is 200 kV and the magnification is 3000-60000.

[0025] In the present invention, preferably, based on the total amount of the catalyst, in the catalyst, 15%≤w(Al2O3)≤35%, for example, it can be 15%, 20%, 25%, 30%, 35% and values ​​between any two groups. The solid acid alkylation catalyst provided by the present invention can realize catalyst molding by controlling the content of alumina in the catalyst with less binder, thereby ensuring that the unit cell constant of the molecular sieve in the catalyst does not decay as much as possible, and the binder is highly dispersible, which can ensure that the solid acid alkylation catalyst has an excellent pore structure and a high acid content.

[0026] In the present invention, from Figure 1 Medium D and Figure 2 As can be seen from D, Figure 1 As shown in D, there is no obvious boundary between the aluminum-based binder and the molecular sieve of the catalyst provided by the present invention, and the d value is small, indicating that the aluminum-based binder and the molecular sieve are evenly mixed and have good dispersion, and no obvious alumina clusters are observed; and as shown in Figure 2As shown in D, the molecular sieve and the aluminum-based binder have a clear boundary, and the d value is small, indicating that the aluminum-based binder and the molecular sieve are unevenly mixed and have poor dispersibility. Preferably, the d value of the catalyst is 0.01-5nm, more preferably 0.01-1nm, for example, it can be 0.01nm, 0.02nm, 0.03nm, 0.04nm, 0.05nm, 0.06nm, 0.07nm, 0.08nm, 0.09nm, 0.1nm, 0.15nm, 0.2nm, 0.25nm, 0.3nm, 0.35nm, 0.4nm, 0.45nm, 0.5nm, 0.55nm, 0.6nm, 0.65nm, 0.7nm, 0.75nm, 0.8nm, 0.85nm, 0.9nm, 0.95nm, 1nm and values ​​between any two groups. The advantage of adopting this preferred embodiment is that it can improve the mixing degree of alumina and molecular sieve to a certain extent, retain the original pore structure of the molecular sieve, and enhance the interaction between the molecular sieve and the alumina binder to increase the acid content.

[0027] In the present invention, preferably, the aluminum-based binder contains at least a portion of free aluminum oxide, and preferably, the catalyst does not contain free aluminum oxide clusters with a particle size exceeding 0.1 nm. It should be noted that free aluminum oxide refers to aluminum oxide clusters that are not in contact with molecular sieve grains, and Figure 2 Obvious alumina clusters can be observed in D, which indicates that the molecular sieve and the aluminum-based binder in the catalyst of the present invention are evenly dispersed. In the solid acid alkylation catalyst provided by the present invention, the particle size of free alumina is relatively small, indicating that the aluminum-based binder has high dispersibility, which is beneficial to improving the catalytic performance of the catalyst.

[0028] In the present invention, the particle size of free aluminum oxide is measured by STEM analysis, and the specific test method is: using a JEM-ARM200F spherical aberration corrected transmission electron microscope. The sample is evenly dispersed with ethanol and then dripped onto a carbon film and dried for testing. The acceleration voltage is 200 kV and the magnification is 3000-60000.

[0029] In the present invention, there is no particular limitation on the type of molecular sieve, and all molecular sieves with regular structures conventionally defined in the art are applicable to the present invention. Preferably, the molecular sieve is an aluminosilicate molecular sieve, preferably at least one selected from A-type molecular sieve, Y-type molecular sieve, X-type molecular sieve, MOR-type molecular sieve and ZSM-5 molecular sieve, more preferably Y-type molecular sieve and / or MOR-type molecular sieve.

[0030] The solid acid alkylation catalyst provided by the present invention has excellent pore structure characteristics. While ensuring a high content of active components of the molecular sieve, the micropore volume accounts for a high proportion, which is beneficial to improving the catalytic performance of the catalyst. Preferably, the micropore volume of the catalyst accounts for more than 60% of the total pore volume, more preferably more than 75%, and more preferably 80-95%.

[0031] In the present invention, the micropore volume of the catalyst is measured by Ar low temperature adsorption method. The specific test conditions are: the sample is vacuumed to 10 -3 Pa, and kept at low temperature for 9 hours to remove water and other impurities adsorbed in the catalyst. The adsorption and desorption of Ar on the purified sample under different pressure ratios p / p0 were tested at liquid nitrogen temperature -196°C. The micropore volume of the sample was then calculated using the HK (Horvath-Kawazoe) method.

[0032] The solid acid alkylation catalyst provided by the present invention has a large specific surface area, which is beneficial to improving the alkylation performance of the catalyst. Preferably, the specific surface area of ​​the catalyst is greater than 400 m 2 / g, more preferably 550-1000m 2 / g, more preferably 550-800m 2 / g.

[0033] In the present invention, the specific surface area of ​​the catalyst is measured by the N2 low temperature adsorption and desorption BET method. The specific test conditions are: the sample is vacuumized at 330°C to 10 -3 Pa, and kept at low temperature for 9 hours to remove water and other impurities adsorbed in the catalyst. The adsorption and desorption of N2 by the purified sample under different pressure ratios p / p0 were tested at liquid nitrogen temperature of -196°C, and the N2 adsorption-desorption isotherm was obtained. The specific surface area was then calculated using the two-parameter BET formula.

[0034] In the present invention, preferably, the total acid content of the catalyst is 1000-5000 μmmol / g, more preferably 2000-4000 μmmol / g. The advantage of adopting this preferred embodiment is that the acid sites of the active component in the catalyst, i.e., the molecular sieve, are well preserved, and the highly dispersed binder interacts with the molecular sieve to enhance the total acid content of the obtained catalyst.

[0035] In the present invention, the total acid content of the catalyst is measured by NH3 programmed temperature desorption, and the specific test conditions are: weigh 0.1g of a sample with a particle size of 20-40 mesh and put it into a sample tube, place it in a thermal conductivity cell heating furnace, use He gas with a flow rate of 50mL / min as a carrier gas to heat it to 600°C and purge it for 1h to remove the adsorbent on the surface of the sample. Then cool it to 100°C, keep the temperature constant for 30min, switch to NH3 / He mixed gas (10% NH3+90% He) for adsorption for 30min, and then switch to He gas to purge for 90min until the baseline is stable to remove NH3 on the sample surface by physical adsorption. Desorption is carried out by heating to 600°C at a heating rate of 10°C / min. The desorption amount of NH3 is measured by a TCD detector during the NH3 desorption process.

[0036] In the present invention, preferably, the framework aluminum index of the catalyst is 33-37, more preferably 35-37. The advantage of adopting this preferred embodiment is that the molecular sieve itself has a complete framework, and the highly dispersed aluminum-based binder can interact well with the molecular sieve to increase the framework aluminum index.

[0037] In the present invention, the framework aluminum index is defined as N-Al, and its calculation formula is: N-Al=192 / (A+1), wherein A is the framework silicon-aluminum ratio, wherein the framework silicon-aluminum ratio of the catalyst is measured by a solid magic angle spinning nuclear magnetic resonance method, and the specific test conditions are: using a 7mm double resonance probe, a Φ7mm ZrO2 rotor. The resonance frequency is 99.3MHz, the magic angle speed is 5kHz, the pulse width is 1.8μs (corresponding to a 20° bevel angle), the cycle delay time is 3s, and the number of scans is about 3000 times.

[0038] In the present invention, preferably, based on the weight of the catalyst, the content of sodium oxide in the catalyst does not exceed 0.5 wt%, preferably does not exceed 0.2 wt%.

[0039] A second aspect of the present invention provides a method for preparing a solid acid alkylation catalyst, wherein the method comprises the following steps:

[0040] (1) subjecting a solid-liquid mixture containing a binder precursor solution and a molecular sieve to a hydrolysis reaction with water, and then performing solid-liquid separation to obtain a solid mixture;

[0041] (2) mixing the solid mixture of step (1) with a peptizing agent, an auxiliary agent and water to form a solid acid alkylation catalyst after drying and calcining;

[0042] The binder precursor is selected from at least one of organic alcohol aluminums.

[0043] The method provided by the present invention comprises the following steps: mixing an organic alcohol aluminum binder precursor solution with a molecular sieve, performing a hydrolysis reaction, and molding. Each step is performed sequentially to improve the dispersion degree of the binder. A solid acid alkylation catalyst with good microporous structure, acidity, and high dispersibility can be prepared through a one-step molding method.

[0044] In the present invention, the type of binder precursor can be selected from a wide range. Preferably, in step (1), the binder precursor is selected from an organic aluminum alcohol having a carbon number less than 15, preferably at least one of aluminum ethoxide, aluminum isopropoxide and aluminum sec-butoxide.

[0045] In the present invention, preferably, in step (1), the binder precursor solution is prepared by dissolving the binder precursor in an organic solvent under ultrasonic conditions. By dissolving the binder precursor in an organic solvent, it is possible to ensure that the resulting material is evenly dispersed during the subsequent hydrolysis reaction.

[0046] In the present invention, the range of organic solvents is relatively wide. Preferably, in step (1), the organic solvent is selected from at least one of methanol, ethanol, isopropanol and sec-butyl alcohol. Preferably, the type of organic solvent is determined according to the type of binder precursor. For example, when the binder precursor is aluminum ethoxide, the organic solvent is ethanol. By this preferred embodiment, the content of impurities in the catalyst can be reduced.

[0047] In the present invention, there is no particular limitation on the amount of the binder precursor and the organic solvent. Preferably, in step (1), the amount of the binder precursor and the organic solvent is such that the mass fraction of the obtained binder precursor solution calculated as oxide is 5-50%, more preferably 10-20%. For example, preferably, the mass ratio of the binder precursor calculated as oxide to the organic solvent is 0.05-0.5:1, preferably 0.1-0.2:1.

[0048] In the present invention, the binder precursor organic alcohol aluminum and the organic solvent are mixed under ultrasonic conditions to form a binder precursor solution, and there is no particular limitation on the mixing conditions, as long as a stable and uniform solution can be obtained. Preferably, in step (1), the ultrasonic conditions include: a temperature of 15-70°C and a time of 1-6h, preferably 2-5h.

[0049] In the present invention, the specific types of molecular sieves have been described in the first aspect and will not be described in detail here.

[0050] In the present invention, preferably, the silicon to aluminum molar ratio of the molecular sieve is 4-5.

[0051] In the present invention, by controlling the dosage of the molecular sieve and the binder precursor solution, the content of the active component of the molecular sieve in the catalyst is high. Preferably, in step (1), the mass ratio of the molecular sieve on a dry basis to the binder precursor solution on an oxide basis is 10:1-2:1, and more preferably 6:1-4:1. Within this preferred range, the content of the active component in the catalyst can be ensured to be high, and the catalyst strength can meet industrial requirements.

[0052] In the present invention, a binder precursor solution is mixed with a molecular sieve to obtain a solid-liquid mixture of a binder precursor solution and a molecular sieve. The present invention does not particularly limit the mixing conditions of the molecular sieve and the binder precursor solution. Preferably, in step (1), the mixing conditions include: a temperature of 25-65°C and a time of 0.5-5h. By mixing the molecular sieve and the binder precursor solution, the binder precursor is highly dispersed, thereby achieving the preparation of a high-strength microporous catalyst material.

[0053] In the present invention, the binder precursor is completely hydrolyzed by adding water and controlling the amount of water added to obtain pseudo-thin aqueous phase alumina with better pore structure properties. Preferably, in step (1), the mass ratio of the solid-liquid mixture containing the binder precursor solution and the molecular sieve to water is 50:1-5:1, and more preferably 50:1-25:1.

[0054] In the present invention, preferably, in step (1), the water is added dropwise to the solid-liquid mixture containing the binder precursor solution and the molecular sieve, and the water drop rate is 0.1-5 drops / s based on the mass of the solid-liquid mixture containing the binder precursor solution and the molecular sieve. In the present invention, by controlling the water addition method, a pseudo-thin aqueous phase alumina with better pore structure properties can be obtained, so that the catalyst still maintains a high micropore ratio and acid content during the subsequent molding process.

[0055] In the present invention, preferably, in step (1), the hydrolysis reaction is carried out in the presence of an alkaline compound, and the alkaline compound is selected from at least one of ammonia water, tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide. The advantage of adopting this preferred embodiment is that the selected alkaline regulator can be easily removed in the subsequent roasting process.

[0056] In the present invention, the conditions for the hydrolysis reaction can be selected in a wide range. Preferably, in step (1), the conditions for the hydrolysis reaction include: a temperature of 40-85°C, a reaction time of 0.5-20h, and a pH of 8-11; further preferably, the conditions for the hydrolysis reaction include: a temperature of 40-80°C, a reaction time of 2-10h, and a pH of 9-11.

[0057] In the present invention, there is no particular limitation on the method of solid-liquid separation in step (1), and for example, it may be filtration, washing, or drying as conventionally defined in the art. In the present invention, there is no particular limitation on the specific operation methods and conditions of filtration, washing, or drying, and those skilled in the art may select them according to actual needs.

[0058] In the present invention, the peptizing agent has a wide range of choices, and any peptizing agent that can play a role in lubrication and pore formation is applicable to the present invention. Preferably, in step (2), the peptizing agent is selected from at least one of hydrochloric acid, nitric acid, oxalic acid and citric acid.

[0059] In the present invention, the amount of the peptizing agent can be selected in a wide range. Preferably, in step (2), the mass ratio of the solid mixture to the peptizing agent is 100-50:1.

[0060] In the present invention, the peptizing agent is present in the form of acid solution. Preferably, the mass concentration of the peptizing agent is 1-10 mass %.

[0061] In the present invention, the range of the auxiliary agent is relatively wide. Preferably, in step (2), the auxiliary agent is selected from at least one of sesbania powder, methyl cellulose, polyether, polyvinyl alcohol, cyclodextrin and chitosan.

[0062] In the present invention, the dosage of the auxiliary agent can be selected in a wide range. Preferably, in step (2), the mass ratio of the solid mixture to the auxiliary agent is 100-50:1.

[0063] In the present invention, there is no particular limitation on the amount of water used in step (2), as long as the solid mixture including the molecular sieve and the binder can be mixed uniformly. Preferably, the ratio of the weight of the water to the total weight of the solid mixture (including the molecular sieve and the binder) on a dry basis is 0.8-1.2:1.

[0064] In the present invention, the drying conditions can be selected in a wide range. Preferably, in step (2), the drying conditions include: a drying temperature of 80-150°C and a drying time of 1-12 hours; more preferably, a drying temperature of 100-150°C and a drying time of 4-8 hours.

[0065] In the present invention, there is no particular limitation on the molding method in step (2). All molding methods conventionally defined in the art are applicable to the present invention, and those skilled in the art can select one according to actual needs.

[0066] In the present invention, the mixed molded product after drying is calcined to remove the additives therein, and the present invention has a wide range of selection of calcination conditions. Preferably, in step (2), the calcination conditions include: a calcination temperature of 450-650°C and a calcination time of 1-12h; more preferably, the calcination temperature is 500-600°C and the drying time is 1-3h.

[0067] In the present invention, preferably, the calcination is performed in an air atmosphere, a nitrogen atmosphere, or a water vapor atmosphere.

[0068] The third aspect of the present invention provides a solid acid alkylation catalyst prepared by the method described in the second aspect.

[0069] The fourth aspect of the present invention provides a use of the solid acid alkylation catalyst described in the first aspect or the third aspect in an alkylation reaction.

[0070] The present invention will be described in detail below by way of examples. In the following examples, all raw materials used are commercially available unless otherwise specified.

[0071] Example 1

[0072] (1) Aluminum isopropoxide (calculated as oxide) and anhydrous ethanol were mixed in a mass ratio of 1:6, the temperature was 65° C., and ultrasonication was performed for 4 h to obtain a uniform and stable solution;

[0073] (2) mixing HY molecular sieve (calculated on a dry basis) with a silicon-aluminum molar ratio of 4.0 with the above solution (calculated on an oxide basis) at a mass ratio of 5:1, stirring at 65° C. for 1 h to obtain a solid-liquid mixture;

[0074] (3) adding pure water to the solid-liquid mixture at a rate of 30 drops / min, wherein the mass ratio of pure water to the solid-liquid mixture is 1:10, adjusting the pH value to 10 with aqueous ammonia, stirring at 65° C. for 1 h, then filtering, washing, and drying at 110° C. for 4 h to obtain a solid mixture;

[0075] (4) Add 3 wt% of sesbania powder and 3 wt% of nitric acid (mass concentration 5%) to the above solid mixture, add pure water in a ratio of water weight to the total dry weight of the solid mixture of 1:1, mix well and extrude into shape, dry at 110°C for 4 hours, and then calcine at 550°C for 3 hours in an air atmosphere to obtain catalyst C-1.

[0076] Figure 1 1 is the TEM-EDX spectrum analysis diagram of the catalyst in Example 1, A is the TEM morphology diagram of the catalyst, B is the aluminum element distribution diagram, C is the silicon element distribution diagram, silicon element only exists in the molecular sieve, and the molecular sieve grains can be determined, and D is the silicon and aluminum element overlap diagram of B and C. Figure 1 It can be seen from A, B and D that there is no obvious boundary between the catalyst molecular sieve provided by the present invention and the aluminum-based binder, and the d value is small, indicating that the molecular sieve and the binder in the catalyst are highly dispersed.

[0077] Figure 3 The MAS NMR of the catalyst in Example 1 is 27 Spectrum. It can be seen from the figure that catalyst C-1 does not show the characteristic peaks belonging to the γ-Al2O3 phase at the chemical shifts of 9ppm and 70ppm, which also shows that the alumina is highly dispersed and does not show aggregated clusters.

[0078] Example 2

[0079] (1) Aluminum isopropoxide (calculated as oxide) and anhydrous ethanol were mixed in a mass ratio of 1:6, the temperature was 45° C., and ultrasonication was performed for 4 h to obtain a uniform and stable solution;

[0080] (2) mixing HY molecular sieve (calculated on a dry basis) with a silicon-aluminum molar ratio of 4.5 with the above solution (calculated on an oxide basis) at a mass ratio of 5:1, stirring at 45° C. for 1 h to obtain a solid-liquid mixture;

[0081] (3) adding pure water to the solid-liquid mixture at a rate of 15 drops / min, wherein the mass ratio of pure water to the solid-liquid mixture is 1:10, adjusting the pH value to 10 with aqueous ammonia, stirring at 65° C. for 1 h, then filtering, washing, and drying at 110° C. for 4 h to obtain a solid mixture;

[0082] (4) Add 3 wt% of sesbania powder and 3 wt% of nitric acid (mass concentration 5%) to the above solid mixture, add pure water in a ratio of water weight to the total dry weight of the solid mixture of 1:1, mix well and extrude into a mold, dry at 110°C for 4 hours, and then calcine the molded carrier at 550°C for 3 hours in an air atmosphere to obtain catalyst C-2.

[0083] Example 3

[0084] (1) Aluminum isopropoxide (calculated as oxide) and anhydrous ethanol were mixed in a mass ratio of 1:6, the temperature was 65° C., and ultrasonication was performed for 4 h to obtain a uniform and stable solution;

[0085] (2) mixing a MOR molecular sieve having a silicon-aluminum molar ratio of 4.0 (calculated on a dry basis) with the above solution (calculated on an oxide basis) in a mass ratio of 6:1, stirring at 65° C. for 1 h to obtain a solid-liquid mixture;

[0086] (3) adding pure water to the solid-liquid mixture at a rate of 30 drops / min, wherein the mass ratio of pure water to the solid-liquid mixture is 1:12, adjusting the pH value to 10 with aqueous ammonia, stirring at 65° C. for 1 h, then filtering, washing, and drying at 110° C. for 4 h to obtain a solid mixture;

[0087] (4) Add 3 wt% of sesbania powder and 3 wt% of nitric acid (mass concentration 5%) to the above solid mixture, add pure water in a ratio of water weight to the total dry weight of the solid mixture of 1:1, mix well and extrude into a mold, dry at 110°C for 4 hours, and then calcine the molded carrier at 550°C for 3 hours in an air atmosphere to obtain catalyst C-3.

[0088] Example 4

[0089] The method of Example 1 was followed, except that in step (3), pure water was added to the solid-liquid mixture at one time, and the other operations remained unchanged. The obtained catalyst was named C-4.

[0090] Example 5

[0091] The method of Example 3 was followed, except that type A molecular sieve (silicon to aluminum molar ratio of 2) was used. The other conditions were consistent with those of Example 3, and the resulting catalyst was named C-5.

[0092] Example 6

[0093] The method of Example 1 is followed, except that in step (2), the mass ratio of HY molecular sieve having a silicon-aluminum molar ratio of 4.5 (calculated on a dry basis) to the stabilized solution of step (1) (calculated on an oxide basis) is 2:1, and the other operations remain unchanged. The resulting catalyst is named C-6.

[0094] Comparative Example 1

[0095] HY molecular sieve with a silicon-aluminum molar ratio of 4.5 and pseudo-boehmite are mixed in a dry weight percentage of 80:20, 3wt% of sesbania powder and 3wt% of nitric acid (mass concentration 5%) are added respectively, and deionized water is added in a ratio of 5:1 between the weight of water and the total dry weight of the other mixtures. After mixing evenly, the mixture is extruded and dried at 110°C for 4h, and then calcined at 550°C for 3h in an air atmosphere to obtain catalyst D-1.

[0096] Figure 2 TEM-EDX spectrum analysis diagram of the catalyst of comparative example 1, A is the TEM morphology diagram of the catalyst, B is the distribution diagram of aluminum elements, C is the distribution diagram of silicon elements, silicon elements only exist in molecular sieves, and molecular sieve grains can be determined, and D is the overlap diagram of silicon and aluminum elements of B and C. Figure 2As can be seen from A, B and D, the catalyst molecular sieve of Comparative Example 1 has a clear boundary with the aluminum-based binder, and the Figure 2 As shown in the middle circle, it indicates that alumina clusters appear in the catalyst of Comparative Example 1.

[0097] Figure 3 is the MAS NMR of the catalyst of Comparative Example 1 27 Spectrum, as can be seen from the figure, catalyst D-1 has characteristic peaks belonging to the γ-Al2O3 phase at chemical shifts of 9ppm and 70ppm, which also indicates that alumina forms aggregated clusters.

[0098] The alumina content and structural parameters of the catalysts prepared in the above examples and comparative examples are shown in Table 1.

[0099] Table 1

[0100]

[0101] Test Case

[0102] The catalysts prepared in the above examples and comparative examples were subjected to alkylation reactions. The results are listed in Table 2. The C8 selectivity represents the average result within the cycle life. The reaction conditions are: the molar ratio of isobutane to 1-butene is 150, the reaction temperature is 75°C, the reaction pressure is 3 MPa, and the mass space velocity of 1-butene is 0.5 h -1 When 1-butene is detected in the product, the catalyst is considered to be deactivated, and the reaction time before the catalyst is deactivated is defined as the catalyst life.

[0103] Table 2

[0104] Catalyst No. Catalyst life (h) <![CDATA[C8 selectivity (%)]]> Example 1 C-1 34 85 Example 2 C-2 32 79 Example 3 C-3 34 78 Example 4 C-4 30 75 Example 5 C-5 28 70 Example 6 C-6 36 82 Comparative Example 1 D-1 12 60

[0105] As can be seen from the above table, the catalyst prepared by the present invention performs excellently in the isobutane-butene alkylation reaction, with a lifespan nearly twice as long as that of comparative example 1, and C8 selectivity can be increased by up to 25 percentage points.

[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A solid acid alkylation catalyst, characterized in that: The catalyst includes a molecular sieve and an aluminum-based binder. Based on the total amount of the catalyst, in the catalyst, 10%≤w(Al2O3)≤40%, w(Al2O3) represents the mass fraction of Al2O3 in the catalyst measured by an XRF method, and the Al2O3 includes aluminum oxide in the aluminum-based binder and aluminum oxide in the molecular sieve; the d value of the catalyst is ≤10nm, and the d value represents the thickness of the aluminum-based binder along the crystal surface edge of the molecular sieve grains in the catalyst measured by a TEM method.

2. The catalyst according to claim 1, wherein Based on the total amount of the catalyst, in the catalyst, 15%≤w(Al2O3)≤35%; Preferably, the d value of the catalyst is 0.01-5 nm, more preferably 0.01-1 nm; Preferably, the aluminum-based binder contains at least a portion of free aluminum oxide, and preferably, the catalyst does not contain free aluminum oxide clusters with a particle size exceeding 0.01 nm.

3. The catalyst according to claim 1 or 2, wherein The molecular sieve is an aluminosilicate molecular sieve, preferably at least one selected from A-type molecular sieve, Y-type molecular sieve, X-type molecular sieve, MOR-type molecular sieve and ZSM-5 molecular sieve, more preferably Y-type molecular sieve and / or MOR-type molecular sieve; Preferably, the micropore volume of the catalyst accounts for more than 60% of the total pore volume, more preferably more than 75%, and even more preferably 80-95%; Preferably, the specific surface area of ​​the catalyst is greater than 400 m 2 / g, more preferably 550-1000m 2 / g; Preferably, the total acid amount of the catalyst is 1000-5000 μmmol / g, more preferably 2000-4000 μmmol / g; Preferably, the framework aluminum index of the catalyst is 33-37, more preferably 35-37.

4. A method for preparing a solid acid alkylation catalyst, wherein: The method comprises the following steps: (1) subjecting a solid-liquid mixture containing a binder precursor solution and a molecular sieve to a hydrolysis reaction with water, and then performing solid-liquid separation to obtain a solid mixture; (2) mixing the solid mixture of step (1) with a peptizing agent, an auxiliary agent and water to form a solid acid alkylation catalyst after drying and calcining; The binder precursor is selected from at least one of organic alcohol aluminums.

5. The method according to claim 4, wherein: In step (1), the binder precursor is selected from an organic aluminum alcohol having a carbon number less than 15, preferably at least one of aluminum ethoxide, aluminum isopropoxide and aluminum sec-butoxide; Preferably, in step (1), the binder precursor solution is prepared by dissolving the binder precursor in an organic solvent under ultrasonic conditions; Preferably, in step (1), the organic solvent is selected from at least one of methanol, ethanol, isopropanol and sec-butanol; Preferably, in step (1), the amount of the binder precursor and the organic solvent is such that the mass fraction of the obtained binder precursor solution calculated as oxide is 5-50%, more preferably 10-20%; Preferably, in step (1), the ultrasonic conditions include: temperature of 15-70°C and time of 1-6h.

6. The method according to claim 4, wherein: In step (1), the molecular sieve is an aluminosilicate molecular sieve, preferably at least one selected from the group consisting of A-type molecular sieve, Y-type molecular sieve, X-type molecular sieve, MOR-type molecular sieve and ZSM-5 molecular sieve, more preferably Y-type molecular sieve and / or MOR-type molecular sieve; Preferably, in step (1), the mass ratio of the molecular sieve calculated on a dry basis to the binder precursor solution calculated on an oxide basis is 10:1-2:1, more preferably 6:1-4:

1.

7. The method according to claim 4 or 5, wherein: In step (1), the mass ratio of the solid-liquid mixture containing the binder precursor solution and the molecular sieve to water is 50:1-5:1, preferably 50:1-25:1; Preferably, in step (1), the water is added dropwise to the solid-liquid mixture containing the binder precursor solution and the molecular sieve, and the dripping rate of the water is 0.1-5 drops / s based on the mass of the solid-liquid mixture containing the binder precursor solution and the molecular sieve; Preferably, in step (1), the hydrolysis reaction is carried out in the presence of an alkaline compound, and the alkaline compound is selected from at least one of aqueous ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide; Preferably, in step (1), the conditions of the hydrolysis reaction include: temperature of 40-85° C., reaction time of 0.5-20 h, and pH of 8-11.

8. The method according to claim 4 or 5, wherein: In step (2), the peptizing agent is selected from at least one of hydrochloric acid, nitric acid, oxalic acid, hydrofluoric acid, fluorosilicic acid and citric acid; Preferably, in step (2), the mass ratio of the solid mixture to the peptizing agent is 100-50:1; Preferably, in step (2), the auxiliary agent is selected from at least one of sesbania powder, methyl cellulose, polyether, polyvinyl alcohol, cyclodextrin and chitosan; Preferably, in step (2), the mass ratio of the solid mixture to the auxiliary agent is 100-50:

1.

9. The method according to claim 4 or 5, wherein: In step (2), the drying conditions include: drying temperature of 80-150° C., and drying time of 1-12 h; Preferably, in step (2), the calcination conditions include: a calcination temperature of 450-650° C. and a calcination time of 1-12 h.

10. A solid acid alkylation catalyst prepared by the method according to any one of claims 4 to 9.

11. Use of the solid acid alkylation catalyst according to any one of claims 1 to 3 and 10 in an alkylation reaction.

Citation Information

Patent Citations

  • Catalytic cracking auxiliary agent containing phosphorus-containing Beta molecular sieve, and preparation method thereof

    CN107971000A

  • Method for preparing tert-butyl glyceryl ether by glycerol etherification

    CN109422627A

  • Preparation method of binder-free hierarchical pore ZSM-5 molecular sieve catalyst

    CN112246274A

  • Alkylation catalyst as well as preparation method and application thereof

    CN114054069A

  • Catalyst, preparation method thereof, and method for prolonging cycle life of catalyst in alkylation reaction

    CN114054071A